Loss of DEK Expression Induces Alzheimer’s Disease Phenotypes in Differentiated SH-SY5Y Cells - Greene, Allie N.; Parks, Lois G.; Solomon, Matia B.; Privette Vinnedge, Lisa M. (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s Disease (AD) is the most common cause of dementia and is characterized by the buildup of β-amyloid plaques and neurofibrillary Tau tangles. This leads to decreased synaptic efficacy, cell death, and, consequently, brain atrophy in patients. Behaviorally, this manifests as memory loss and confusion. Using a gene ontology analysis, we recently identified AD and other age-related dementias as candidate diseases associated with the loss of DEK expression. DEK is a nuclear phosphoprotein with roles in DNA repair, cellular proliferation, and inhibiting apoptosis. Work from our laboratory determined that DEK is highly expressed in the brain, particularly in regions relevant for learning and memory, including the hippocampus. Moreover, we have also determined that DEK is highly expressed in neurons. Consistent with our gene ontology analysis, we recently reported that cortical DEK protein levels are inversely proportional to dementia severity scores in elderly female patients. However, the functional role of DEK in neurons is unknown. Thus, we knocked down DEK in an in vitro neuronal model, differentiated SH-SY5Y cells, hypothesizing that DEK loss would result in cellular and molecular phenotypes consistent with AD. We found that DEK loss resulted in increased neuronal death by apoptosis (i.e., cleaved caspases 3 and 8), decreased β-catenin levels, disrupted neurite development, higher levels of total and phosphorylated Tau at Ser262, and protein aggregates. We have demonstrated that DEK loss in vitro recapitulates cellular and molecular phenotypes of Alzheimer’s disease pathology.